The effect of nonlinear wave-structure and soil-structure interactions in the design of an offshore structure. (March 2017) - Chatziioannou, Konstantinos; Katsardi, Vanessa; Koukouselis, Apostolos; Mistakidis, Euripidis
Abstract: This work highlights the importance of the consideration of nonlinearities in the analysis and design of deep water platforms. The nonlinearities concern both the calculation of the wave loading and the structural analysis of the platform. More specifically, numerical calculations have been undertaken using a fully nonlinear three-dimensional wave model capable of accurately representing a realistic distribution of wave energy in both frequency and direction. The purpose of these calculations is to provide what is essentially a benchmark against which to assess the accuracy of the commonly applied design wave solutions; linear and 2nd order random waves and linear and nonlinear steady wave solutions. On the other hand, in the field of structural analysis, three cases are considered for comparison, linear analysis, nonlinear analysis with the nonlinearity limited to the modelling of the soil and finally, geometrically nonlinear analysis with nonlinear modelling of the soil. The calculations are performed using the well-known structural analysis software SAP2000, enhanced with an interface that was developed in order to calculate the forces due to wave loading and apply them on the structural members. The example treated in the context of the present paper is a compliant tower, set-up in deep water. The results show that for the specific environmental conditions and for the structure examined herein, the consideration of the nonlinear particle kinematics in the wave loading and the consideration of the structural nonlinearities leads to significant differences with respect to the common design methods in both the displacements and stresses of the structure. Moreover, irrespectively of the adopted wave theory, the structural nonlinear analyses lead to significant discrepancies from the linear ones. Highlights: The impact of nonlinearities in the design of an offshore platform is investigated. Steady wave theories underestimate both base shear and overturning moment. Random wave theories lead to slight overestimation of response. Soil nonlinear behaviour has a great impact on the response of the structure. Second order effects have a less severe effect on the overall response.